The high and middle molecular weight neurofilament subunits regulate the association of neurofilaments with kinesin: Inhibition by phosphorylation of the high molecular weight subunit - Jung, Cheolwha; Lee, Sangmook; Ortiz, Daniela; Zhu, Qinzhang; Julien, Jean-Pierre; Shea, Thomas B. (Brain research. Molecular brain research., 2005)
Kinesin participates in axonal transport of neurofilaments (NFs), but the mode by which they attach to kinesin is unclear. We compared the association of NFs with kinesin in mice expressing or lacking NF-H or NF-M. In normal and M−/− mice, the leading edge of metabolically labeled NF subunits was selectively co-precipitated with kinesin. By contrast, the entire wave of radiolabeled subunits co-precipitated with kinesin in H−/− mice. Similar bulk levels of NFs co-precipitated with kinesin from normal and H−/− mice, but reduced levels co-precipitated from M−/− mice. These data suggest that both NF-H and NF-M regulate the association of NFs with kinesin. They further indicate that phosphorylation of NF-H dissociates NFs from kinesin and provides a mechanism by which NF-H phosphorylation can contribute to the slowing of NF axonal transport.